National identity attributes as desired future image of a nation - Handayani, Bintang; Rashid, Basri (IDOSI Publications, 2015)
Although national identity attributes can be used for nation building and branding the nation, little study has been explored on enriching branding the nation perspectives.This study aims to demystify the role of national identity attributes as a nation desired future image. Utilizing interview for exploratory pre-test and followed by field survey, Indonesia national identity attributes are explored. The finding indicates that national identity attributes may be emerged as the essence elements for developing the desired future image of a nation. Particularly, this study suggests for desired future image to be established, the inclusion of self-perception must be in line with the actual projected image. Overall, this study highlights the importance of national identity attributes as desired future image of nation, which is useful for mapping a nation’s positioning. Therefore, it is deemed appropriate to strategically integrate self-perception and the actual projected image.